Pampering parties planning a party that makes your friends say "ahhh" - Jones, Jen (North Mankato, MN Capstone Press, 2014)
Lots of kids love parties, and this series will help them add to their fun. With plenty of inspiration and information, Perfect Parties includes creative themes, decorating ideas, and party planning tips"--
A gift from book Africa
Games & Recreations
1 2 13 15
Keywords: Children's parties -- Planning -- Juvenile literature; Parties -- Planning